Perancangan Aplikasi Pencatatan Transaksi Keuangan dan Inventory Berbasis Android Distributor Produk MSL Purbalingga - Ali Nur Ikhsan; Adam Prayogo Kuncoro; Alfiansyah Arifudin Akbar (Universitas Asahan, 2020)
Abstract - The MSL Purbalingga distributor is located in Dusun IV Wanakerta, Banjarkerta, Karanganyar sub-district, Purbalingga District, Central Java. The products available at the MSL Purbalingga Distributor include softeners and fragrances, liquid detergents, softeners, and super laundry perfume. The product prices are determined based on the type of containers, such as bottles, refills, and sprays. But currently, the administration system at the MSL Purbalingga Distributor still uses records in the form of ledgers so that there are deficiencies, namely the accumulation of book archives and transaction record data is less secure. The process of recording transactions and making administration reports within a certain period of time is difficult and even creates administrative problems. With the development of Android technology, it can be used in recording transactions for the MSL Distributor with the aim of simplifying administration, as well as in business matters. In terms of simplifying business affairs, information technology can be used as an administrative recording medium for MSL Distributors in carrying out all aspects of sales transaction activities. The current research focuses on the design and implementation of transaction recording and inventory applications at the location of the Purbalingga MSL agent distributor. The results of the application of this mobile application for recording transactions and inventory are a benefit for research partners, namely, it makes it easier to record and store data compared to the old method of recording using manual books. The application of this mobile application was declared successful after the testing process was carried out at the research partner's location by applying the Black Box testing method. Keywords - Android Mobile Application, Cloud Computing, Application Collecting Abstrak - Distributor MSL Purbalingga terletak di Dusun IV Wanakerta, Banjarkerta, Kec. Karanganyar, Kab. Purbalingga, Jawa Tengah. Produk yang tersedia pada Distributor MSL Purbalingga diantaranya pelicin dan pewangi, detergen cair, softener, dan parfum laundry super. Harga produk ditentukan berdasarkan jenis wadah, seperti botol, refill dan spray. Tetapi saat ini sistem pembukuan pada Distributor MSL Purbalingga masih menggunakan pencatatan berupa buku besar sehingga terdapat kekurangan yaitu penumpukan arsip buku serta data catatan transaksi kurang aman. Proses pencatatan transaksi dan pembuatan laporan pembukuan dalam kurun waktu tertentu sulit dilakukan, bahkan menimbulkan permasalahan administrasi. Dengan perkembangan teknologi android dapat dimanfaatkan dalam kegiatan pencatatan transaksi Distributor MSL dengan tujuan mempermudah administrasi, serta dalam urusan bisnis. Dalam hal mempermudah urusan bisnis, teknologi informasi dapat dijadikan media pencatatan administrasi bagi Distributor MSL dalam menjalankan segala aspek aktifitas transaksi penjualan. Penelitian saat ini berfokus pada perancangan dan implementasi aplikasi pencatatan transaksi dan inventory di lokasi Distributor agen MSL Purbalingga. Hasil pada penerapan aplikasi mobile pencatatan transaksi dan inventory ini menjadi manfaat bagi mitra penelitian yaitu memudahkan pencatatan serta penyimpanan data dibandingkan dengan metode pencatatan yang lama menggunakan buku manual. Penerapan aplikasi mobile ini dinyatakan berhasil setelah dilakukan proses pengujian di lokasi mitra penelitian, dengan menerapkan metode Black Box testing.Kata Kunci - Aplikasi Mobile Android, Cloud Computing, Aplikasi Pendataan